Exploring the role of nutritional strategies to influence physiological and cognitive mechanisms in cold weather operations in military personnel - Smid, Dagmar J.; Klous, Lisa; Ballak, Sam B.; Catoire, Milène; De Hoogh, Iris M.; Hoevenaars, Femke P. M. (Frontiers in Physiology, 2025)
IntroductionAs a basis for performance optimal nutritional balance is key to keep the body functioning at homeostatic capacity. When environmental circumstances become challenging such as in a cold environment extraordinary performance is requested specifically for physiological (i.e., vascular response, diet induced thermogenesis, immune response), and cognitive mechanisms (i.e., cognitive function, psychological and cognitive wellbeing) of the human body. In this review we describe which nutritional strategies could enhance military performance in the cold by mitigation of CWIs.MethodsWe will first describe how exposure to cold affects the physiological or cognitive mechanisms itself and then we will explain how nutrition can be used to optimize these affected mechanisms. We will discuss long-term nutritional solutions preventing shortfalls and potential direct quick fixes for physiological and cognitive mechanisms.ResultsFor optimal functioning of the immune system and infection prevention, absence of micronutrient deficiencies is key and should be pursued amongst military personnel. For the effectivity of PUFA’s, Echinacea purpurea and probiotics in immune functioning, more research is needed in the CWO context. A multitude of micronutrients (i.e., nitrate, L-citrulline, L-arginine) appears to be able to enhance vasodilation, perhaps partially offsetting the detrimental effect of cold on peripheral blood circulation. Although the direct effect of diet induced thermogenesis is small in comparison to being physically active, it is of interest to investigate the effects of adding a combination of spices to the rations, such as capsaicin from red pepper, cinnamon, ginger, and menthol. Also, of interest for stimulation of thermogenesis are caffeine, and polyphenolic compounds. Caffeine and tyrosine supplementation 1 h, resp. 2 h before a cognitively demanding task during CWOs could be used to mitigate decreases in cognitive performance. Alternatives that are of interest, but need more research, include chocolate polyphenols and omega-3 fatty acids.ConclusionEven though some recommendations can be provided, it is evident that much information regarding the effectiveness and application of micronutrients in cold weather operations is still lacking. More focus should be placed on investigating (micro)nutritional solutions, practical feasibility, and implementation in operational military personnel to better understand the magnitude of the possible benefits in cold conditions.